PRIORITY DIRECTIONS FOR ENHANCING YOUTH PATRIOTISM IN THE CONDITIONS OF NEW UZBEKISTAN (American Journal of Research in Humanities and Social Sciences, 2026)
This article analyzes the priority directions for enhancing youth patriotism in the context of New Uzbekistan from a socio-philosophical perspective. In the context of globalization and digital transformation, the issues of forming national identity, civic responsibility, and patriotic values among young people are examined. The study highlights the role of the education system, mass media, social networks, and state policy in shaping youth upbringing. The author proposes improving spiritual and educational activities, introducing innovative approaches, and ensuring the harmony of national and universal values as key priority directions for strengthening youth patriotism.